2017
DOI: 10.1007/s00277-017-3125-4
|View full text |Cite
|
Sign up to set email alerts
|

High level of soluble interleukin-2 receptor in serum predicts treatment resistance and poor progression-free survival in multiple myeloma

Abstract: The IL-2/IL-2 receptor (IL-2R) system plays a central role in maintaining normal T cell immunity, and its disturbance is associated with several hematologic disorders. Studies have found in several types of lymphoma that abnormal amounts of soluble IL-2R (sIL-2R) may result in imbalance of the IL-2/IL-2R system and hence of the T cell immunoregulation. Whether the level of sIL-2R in blood could predict treatment outcomes or not needs to be investigated in multiple myeloma (MM) patients. The level of sIL-2R in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…To our best knowledge, our study is the first one indicating sCD25 as a useful marker that could be easily measured and indicate patients with NSCLC who would not benefit from immunotherapy with ATEZO or PEMBRO. Worth noting is that we obtained a similar cut-off for baseline sCD25 (5.99 ng/mL) as Cabrera et al [25] (5.80 ng/mL) and Wang et al [22] (6.05 ng/mL), who found correlations between the elevated sCD25 levels and shorter OS or PFS in other types of cancers.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…To our best knowledge, our study is the first one indicating sCD25 as a useful marker that could be easily measured and indicate patients with NSCLC who would not benefit from immunotherapy with ATEZO or PEMBRO. Worth noting is that we obtained a similar cut-off for baseline sCD25 (5.99 ng/mL) as Cabrera et al [25] (5.80 ng/mL) and Wang et al [22] (6.05 ng/mL), who found correlations between the elevated sCD25 levels and shorter OS or PFS in other types of cancers.…”
Section: Discussionsupporting
confidence: 64%
“…Data from the literature show that while the sCD25 protein level is not affected by gender in healthy individuals [45,46], it may be disease-specific [42]. Although some authors reported that serum sCD25 increased with age [27,46,47], others obtained contradictory results [22,42]. We observed no difference in baseline sCD25 between older and younger individuals.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…У пациентов с ММ с прогрессией заболевания и рефрактерностью к проводимой химиотерапии на первичном этапе диагностики выявлено значимое превышение уровней IL-2 (p=0,001), IL-6 (p=0,006), TNF (p=0,000), которые, по литературным данным, коррелируют с активностью процесса и тяжестью заболевания [17,18]. ЗАКЛЮЧЕНИЕ Данные о прогностических факторах при ПН могут являться основополагающими в вопросах назначения специфической терапии и должны определять направление дальнейших исследований.…”
Section: оригинальные исследования Original Researchunclassified
“…Multivariate survival analysis indicates that sIL-2R levels are an independent prognostic factor for PFS. Furthermore, based on subgroup analysis results, high levels of sIL-2R are associated with poor PFS in MM patients (29). IL-2 can not only stimulate NK and T cell growth and enhance cytolytic action strongly, but also sensitizes T cells to activation-induced cell death and is required for Treg cells to reduce persistent immune responses (82).…”
Section: Sil-2rmentioning
confidence: 99%